O processo de disciplinarização da escrita no ensino médio brasileiro: implicações didático-pedagógicas e político-sociais - Dametto, Fabiana Veloso de Melo (2020)
This study, linked to the research line Language in Social Context, from the Language Postgraduate Program of the Federal University of Santa Maria, aims at analyzing the disciplinarization process of school writing in Brazilian High School (HS) critically and from a socio-historical approach. This theme rises from the observation that, unlike main official guidelines for Basic Education (BE) - PCNEM, OCNEM and DCNEM – various schools, especially private ones, have included a “new” subject in their curriculum, denominated Essay or Text Production. Therefore, this manner of fragmenting the Portuguese language teaching objects has been consolidating silently and apart from the public policies and academic discussions. Besides the evident divergence between official prescriptions and school practices, this study also investigates and reflects upon possible didactic-pedagogical and politicalsocial implications resulting from this partition, through which privileged time and space are set for teaching school writing, which becomes a curricular component that is independent from the Portuguese language. This problem is justified insofar the teaching political role and dimension are admitted. From this perspective, the existence of each subject in school curriculum is seen as the result of a long and complex constitution path, in which diverse forces and mostly conflicting are at stake (political, social, cultural, pedagogical and market forces, for instance). Because of this assumption, I defend the thesis that the insertion of a subject of such nature in school curriculum may cause changes that, for they disrupt the course of other subjects and historically established practices, may impact the final result of Portuguese language teaching work. Therefore, I believe this is an indeed complex practice and, because of that, it was necessary to investigate internal and external factors related to school that have been providing its emergence, maintenance, continuity and consequences at school. The theoretical frameworks of this study are: 1) the History of School Subjects; and 2) the socio-historical approach of Volóchinov/Bakhtin. Along with these theories, I take documentary (official documents) and bibliographical (studies in which the history of the last fifty years of Portuguese language teaching in Brazil is brought together) evidence. Based on results obtained, stating that pedagogical practices in this area in Brazilian Basic Education have been fragmented for a long time is coherent; and the work with writing, even within Portuguese language subject, has always been enveloped in a theoretical and methodological nebula, which persists until today. The investigation undertaken allowed the raising of hypotheses regarding the network of factors and aspects that possibly permeate the genesis, the function and the functioning of the school writing subject currently. In order to conclude this study, I point out and problematize likely implications of this practice for teaching and learning Portuguese language in Brazilian High School.